Terahertz Nonlinear Optics of Graphitic Materials: From THz Pulse Manipulation to High-Harmonic Generation - Maleki, Ali (Université d'Ottawa | University of Ottawa, 2025)
This thesis investigates the nonlinear optical behavior of graphitic materials in the terahertz (THz) frequency regime, with a focus on enhancing and understanding strong-field light–matter interactions in graphene and its derivatives, including graphene oxide (GO) and its reduced forms. By integrating theoretical modeling, numerical simulations, device fabrication, and experimental investigations of nonlinear THz phenomena, this work explores THz pulse manipulation and establishes a comprehensive platform for scalable and tunable THz nonlinear photonics. We begin by establishing the theoretical foundations of THz nonlinear optics, including the derivation of the nonlinear wave equation, analysis of second- and third-order polarization responses, and the dynamics of carrier heating and saturable absorption in Dirac materials such as graphene. These concepts are experimentally realized using a high-field table-top THz system based on tilted-pulse-front optical rectification and electro-optic sampling. A key challenge in this regime—the detection of weak nonlinear signals amid broadband excitation in a noisy system—is addressed through the design and fabrication of metamaterial-based THz spectral filters featuring octave-wide bandwidths and high extinction ratios. These custom-built devices are engineered to shape the spectral content of the THz beam, enhance spectral isolation, and significantly improve detection sensitivity. In particular, a configuration of lowpass and highpass filters is developed to selectively transmit generated harmonic signals while suppressing the strong pump background, enabling reliable measurement of weak high-harmonic generation in subwavelength 2D samples. Using this system, we demonstrate a multi-strategy platform for enhancing third-harmonic generation (THG) in graphene, integrating three complementary approaches: (i) stacking decoupled multilayer graphene sheets to increase the light–matter interaction length, (ii) applying electrical gating to dynamically modulate carrier density and optimize nonlinear conductivity, and (iii) coupling graphene with plasmonic metasurfaces to achieve strong local field enhancement. The synergy of these strategies leads to up to two orders of magnitude enhancement in THG efficiency, underscoring the critical role of both structural and electronic tunability. Despite these gains, further improvement is limited by graphene’s intrinsic linear absorption, which restricts the effective interaction length beyond a few layers. This motivates the use of alternative low-loss, tunable materials such as graphene oxide (GO), which combines reduced THz absorption, chemical flexibility, and access to nonlinear regimes beyond those of pristine graphene. We next explore GO, a chemically functionalized derivative of graphene that features lower THz absorption and local symmetry breaking due to the presence of oxygen-containing functional groups. These groups can be gradually removed through chemical or thermal reduction, allowing for continuous tuning of GO’s optical properties. Our experiments reveal a distinct nonlinear regime in GO, marked by the coherent generation of both odd and even-like harmonics, as well as a unique saturable transmission behavior under intense THz excitation. To interpret these effects, we develop a phenomenological two-level system model that accurately captures the field-dependent transmission response. This analysis identifies saturable transmission as a new symmetry-defying mechanism for wave mixing in functionalized 2D materials, enabling the generation of even-like harmonics without requiring long-range structural asymmetry. Together, the results presented in this thesis establish graphitic materials—both pristine and functionalized—as versatile platforms for advancing nonlinear optics in the terahertz regime. By combining material engineering, device fabrication, and nonlinear spectroscopy, this work delivers a unified framework for probing and enhancing THz-driven light–matter interactions in 2D systems. The multi-strategy enhancement approaches for graphene, the discovery of novel nonlinear behavior in graphene oxide, and the implementation of spectral filtering and modeling tools all contribute to a powerful experimental and theoretical platform. This platform not only deepens our understanding of strong-field physics in low-dimensional materials, but also lays the groundwork for next-generation THz photonic technologies, including reconfigurable frequency converters, modulators, and integrated nonlinear devices.
Keywords: Graphitic Materials